2009
DOI: 10.1186/1471-2407-9-125
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of apoptosis proteins (IAPs) expression and their prognostic significance in hepatocellular carcinoma

Abstract: BackgroundSimilarly to other tumor types, an imbalance between unrestrained cell proliferation and impaired apoptosis appears to be a major unfavorable feature of hepatocellular carcinoma (HCC). The members of IAP family are key regulators of apoptosis, cytokinesis and signal transduction. IAP survival action is antagonized by specific binding of Smac/DIABLO and XAF1. This study aimed to investigate the gene and protein expression pattern of IAP family members and their antagonists in a series of human HCCs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
106
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 36 publications
9
106
0
Order By: Relevance
“…By contrast, survivin mRNA and protein were undetectable in adjacent paraneoplastic tissues (7). Studies by Yang et al (8), Zhu et al (9) and Hui et al (10) that used immunohistochemical staining, as well as studies by Chau et al (11) and Augello et al (12) that used RT-PCR analysis, confirmed the elevated levels of survivin in HCC tissues. These studies indicated that survivin protein was a promising histological tumor marker.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…By contrast, survivin mRNA and protein were undetectable in adjacent paraneoplastic tissues (7). Studies by Yang et al (8), Zhu et al (9) and Hui et al (10) that used immunohistochemical staining, as well as studies by Chau et al (11) and Augello et al (12) that used RT-PCR analysis, confirmed the elevated levels of survivin in HCC tissues. These studies indicated that survivin protein was a promising histological tumor marker.…”
Section: Discussionsupporting
confidence: 59%
“…By contrast, survivin mRNA and protein were undetectable in adjacent paraneoplastic tissues (7). Since then, a number of studies have also identified an elevation in the level of survivin in HCC tissues using immunohistochemical staining (8-10) and 12). These findings indicate the potential value of survivin in the diagnosis of HCC.…”
Section: Introductionmentioning
confidence: 87%
“…Increased survivin expression in cancer patients is an unfavorable prognostic marker correlating with decreased overall survival in several malignancies, including lung (33,34), gastric (35), colorectal (18), and breast carcinomas (14), hepatocellular carcinoma (36) as well as in pediatric solid tumors such as neuroblastoma (37), and hepatoblastoma (23). Relationship between survivin expression and RMS are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported livin expression in fetal and some tumor cell lines and primary tumors (Augello et al, 2009;Dasgupta et al, 2010;El-Mesallamy et al, 2011). Kasof and Gomes (2001) reported high expression of the α-isoform in several melanoma cell lines and primary melanoma tumors.…”
Section: Introductionmentioning
confidence: 99%